1999
DOI: 10.1210/jcem.84.1.5415
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Assay for Thyrotropin Receptor Antibodies Has Superior Diagnostic Sensitivity for Graves’ Disease

Abstract: Detection of autoantibodies to the TSH receptor (TSH-R) in Graves' disease has found widespread use in clinical routine and is performed mostly by commercial RRAs measuring TSH binding inhibitory activity. We report in this study on a second generation TSH binding inhibitory assay using the human recombinant TSH-R with two major improvements: 1) superior diagnostic sensitivity for Graves' disease, and 2) for the first time, nonradioactive and radioactive coated tube (CT) technology. Full-length human recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
121
1
20

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 44 publications
13
121
1
20
Order By: Relevance
“…Swedish studies from the 1970s and 1980s report somewhat higher relapse rates than our study (7,20) even though definite ablative methods were used more frequently, and that would supposedly lead to fewer and more easily ATD-treated patients at that time. However, TRAb methods are more sensitive today (26), probably affecting the number of patients diagnosed with GD by such assays, as used in 2004 in our study, and may have a better prognosis with ATD. This study reflects the practice in the real world of routine care at district and central hospitals where analysis of TRAb was not part of the clinical decision on if or when to end ATD treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Swedish studies from the 1970s and 1980s report somewhat higher relapse rates than our study (7,20) even though definite ablative methods were used more frequently, and that would supposedly lead to fewer and more easily ATD-treated patients at that time. However, TRAb methods are more sensitive today (26), probably affecting the number of patients diagnosed with GD by such assays, as used in 2004 in our study, and may have a better prognosis with ATD. This study reflects the practice in the real world of routine care at district and central hospitals where analysis of TRAb was not part of the clinical decision on if or when to end ATD treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Most related studies have been performed using the first-generation TBII assay and yet second-generation assays are nowadays widely available. Instead of solubilized porcine receptors (14,15), these newer assays use recombinant TSHR coated on a solid-phase surface which provides a markedly improved sensitivity and specificity (16,17,18). To our knowledge, the threshold value indicating a risk for fetal or neonatal autoimmune hyperthyroidism with a second-generation TBII assay has only been investigated in one small study (19).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a high specificity (nearly 100%), these assays show a low diagnostic sensitivity, ranging from 52% to 94% (with a mean of 77.5%) in the most relevant literature reports of the last 20 years [10,[12][13][14][15][16][17][18][19][20] (Table 1). As a consequence, a significant proportion (6-48%; mean 22.5%) of GD patients with clinical HT were reported to be TRAb 'negative' by first-generation methods.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the sensitivity of the TRAb assay, secondgeneration immunoassays that use monoclonal antibodies (mAb), human or porcine TSHR immobilized on a plastic surface and bovine TSH labelled with 125 I, or acridinium ester, or with biotin-streptavidin-peroxidase have become available [15,21]. Several studies have shown that the clinical sensitivity of these assays increases to a mean of 95.9% (range 72.6-100%; Table 1) with a small decrease in specificity (97.9%, range 91.4-100%) [15,[17][18][19][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%